Utilization of neurological dominance science (NDS) to enhance students’ creativity in communication as implementation outcome based education (OBE) - Meisuri, Meisuri; Hartati, Rita (Politeknik Negeri Bali, 2023)
This study aims to investigate the contribution of the Neuro Dominance Science (NDS) program in improving students' creative communication skills and the completion of six tasks as a result of the Indonesian National Qualifications Framework called KKNI, with six (6) tasks of KKNI. This study uses qualitative and quantitative method in analyzing the data. The participants in this study were 50 students of English language and Literature Department, Universitas Negeri Medan that completed NDS workshop as one of the programmed of Creative Innovative Communication (CIC) subject at the fourth Semester. Data was collected through a questionnaire made in the form of a Google form to measure students' creative communication abilities and completion of KKNI assignments. The results of this study indicate that the NDS program has a significant contribution to improving students' creative communication skills. Quantitative data analysis shows an increase in scores on creative communication assessment after students join the NDS program. In addition, the NDS program also assists students in completing the six tasks required by the KKNI, such as problem-solving, critical thinking, and collaboration. This research provides valuable insight into the contribution of the NDS program in improving students' creative communication skills and completing KKNI assignments. The results of this study can be used by policymakers and educators to consider implementing the NDS program in schools as an effort to improve students' skills in creative communication and achievement of KKNI tasks.